Silikon v protetiki in ortotiki - Maver, Tomaž (Rehabilitacija (Ljubljana), 2019)
Silicone has been in relatively frequent use in the field of prosthetics and orthotics since 1987. At first, it was used in dental prosthetics, later for producing facial epitheses, and only lately it has become prominent in the production of prostheses for people after partial finger amputation, hand amputation, foot amputation and - to a lesser extent - in orthotics. The development of different types of silicone lead to development of different technologies, ranging from pouring silicone into casts to direct modelling of silicone on the patient. These procedures nowadays enable the production of standard (i.e., serial) as well as individually made orthotic and prosthetic aids. The aim of the paper is to give an overview of where silicone is most frequently and effectively used nowadays within prosthetics and orthotics, with an emphasis on individually designed aids.
Keywords: aesthetic prostheses; anaplastologija; anaplastology; epiteze; epitheses; estetske proteze; Orthotic Devices; Prostheses and Implants; silicone; silikon